2020
DOI: 10.1590/1980-265x-tce-2018-0422
|View full text |Cite
|
Sign up to set email alerts
|

The Meaning of Labor Activities for Young Women With Breast Neoplasms

Abstract: Objective: to understand the meaning of work activities for young women with breast cancer. Method: a qualitative study that used as a theoretical framework the Symbolic Interactionism and, as the methodological framework, the Discourse of the Collective Subject. It was developed in a mastology outpatient clinic and a mastectomized rehabilitation center whose data collection took place between February 2014 and January 2015. Twelve women between 18 and 40 years old with up to one year of diagnosis of breast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
1
2
0
1
Order By: Relevance
“…Other problems related to family and financial obligations were noted by the study participants. These difficulties corroborate the findings in other papers on the RTW among breast cancer survivors (Magalhães et al, 2020;Stergio-Kita et al, 2014). The survivors in our study, being under 50, were confronted with issues associated with their younger age, such as the fear of recurrence and the lack of adequate social support.…”
Section: Factors Related To Breast Cancer Survivalsupporting
confidence: 91%
“…Other problems related to family and financial obligations were noted by the study participants. These difficulties corroborate the findings in other papers on the RTW among breast cancer survivors (Magalhães et al, 2020;Stergio-Kita et al, 2014). The survivors in our study, being under 50, were confronted with issues associated with their younger age, such as the fear of recurrence and the lack of adequate social support.…”
Section: Factors Related To Breast Cancer Survivalsupporting
confidence: 91%
“…A study (23) conducted in an outpatient mastology clinic in the countryside of the state of São Paulo, Brazil, found that the diagnosis of cancer at a working age led the sample studied to be concerned about their personal and family finances and changes in their lifestyle. This fear may be more evident in women who live alone with their children, as they are the ones who have to support the household.…”
Section: Resultsmentioning
confidence: 99%
“…D'autres problèmes inhérents à leurs obligations familiales et financières ont été rapportés par les participantes. Ces difficultés corroborent celles évoquées dans d'autres écrits portant sur le RAT chez les survivantes du cancer du sein (Magalhães et al, 2020;Stergio-Kita et al, 2014). Selon nos résultats, ces survivantes de moins de 50 ans font face à des enjeux liés à leur jeune âge tels que la peur de la récidive ainsi que l'absence du soutien social adapté.…”
Section: Discussionunclassified